Self-Resilience of Patients with Systematic Lupus Erythematosus (SLE): Literature Review - Khoiriya, Salma Maulida; Rahayu, Sri (Jurnal Keperawatan Profesional, 2026)
Systemic Lupus Erythematosus (SLE) is a chronic autoimmune disease characterized by complex clinical pathways that significantly impact both physical and psychological domains. Effective SLE management necessitates the integration of self-resilience into clinical practice as a strategic tool for healthcare providers in hospitals and long-term care settings to mitigate emotional distress. This article aims to review and analyze the mechanisms of self-resilience in SLE patients and its practical utility for healthcare professionals. Methods a literature review was conducted using PubMed, ScienceDirect, Google Scholar, and Garuda databases for the 2021–2026 period. This timeframe was selected to capture post-pandemic patient management dynamics relevant to contemporary digital healthcare advancements. Inclusion criteria comprised quantitative and qualitative studies with robust methodologies, including cross-sectional or experimental designs and representative sample sizes. Findings indicate that self-resilience dynamically enhances quality of life through adaptive coping mechanisms that reframe perceived threats into challenges. Furthermore, self-management strengthens patient self-efficacy, while social support serves as a critical buffer against physical stressors. Resilience is a vital component of holistic care. Healthcare professionals are encouraged to adopt psychosocial approaches, utilizing validated instruments such as the Connor-Davidson Resilience Scale (CD-RISC) for routine screening. The implementation of community-based support groups and psychoeducational interventions is essential to bolster patient adaptation capacity in both clinical and independent settings